2023
DOI: 10.1021/acs.energyfuels.2c04316
|View full text |Cite
|
Sign up to set email alerts
|

Bication Thiocyanate Salts for Advanced Performance of Wide-Band Gap Perovskite Solar Cells

Abstract: Organohalide perovskite materials with a high band gap of over 1.65 eV are employed in tandem photovoltaic cells, but higher defect density, deeper trap states, and halide separation in the perovskites limit the performance of all of the tandem cells. In this study, a thiocyanate (SCN)-based ionic liquid, 1-butyl-3methylimidazolium thiocyanate (BMI-Th), was added to the perovskite material to improve its performance and stability. BMI-Th-added perovskite solar cells (PSCs) display higher power conversion effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Introducing anions of organic structures, such as thiocyanate ions, is a common method for improving their crystallization ability and surface morphology in PSCs. 64–70 As early as 2015, Jiang et al replaced the two iodines in CH 3 NH 3 PbI 3 with amphoteric halides of thiocyanate (SCN − ), and fabricated PSCs related to CH 3 NH 3 Pb(SCN) 2 I by a simple spin-coating process, which generally maintained a lattice structure similar to halogen perovskites due to thiocyanate ions. 71 In addition, in 2016, Tai et al used a simple precursor solution treatment method to show that PSCs are prepared under environmental conditions using the lead( ii ) thiocyanate (Pb(SCN) 2 ) precursor, and high-quality CH 3 NH 3 PbI 3− X (SCN) X perovskite films can be easily prepared even if the relative humidity exceeds 70%.…”
Section: Halide Perovskite Solar Cellsmentioning
confidence: 99%
“…Introducing anions of organic structures, such as thiocyanate ions, is a common method for improving their crystallization ability and surface morphology in PSCs. 64–70 As early as 2015, Jiang et al replaced the two iodines in CH 3 NH 3 PbI 3 with amphoteric halides of thiocyanate (SCN − ), and fabricated PSCs related to CH 3 NH 3 Pb(SCN) 2 I by a simple spin-coating process, which generally maintained a lattice structure similar to halogen perovskites due to thiocyanate ions. 71 In addition, in 2016, Tai et al used a simple precursor solution treatment method to show that PSCs are prepared under environmental conditions using the lead( ii ) thiocyanate (Pb(SCN) 2 ) precursor, and high-quality CH 3 NH 3 PbI 3− X (SCN) X perovskite films can be easily prepared even if the relative humidity exceeds 70%.…”
Section: Halide Perovskite Solar Cellsmentioning
confidence: 99%
“…The detailed study indicated that the carboxyl and amino groups at the opposite ends of 3gpa Fig. 8 Chemical structures of BMIMSCN, 65,66 IdMe, IdH (BMIMBF 4 ), 67,87,109 EMIMAc, 68 DPPIQPF 6 , 69 SBPPF 6 , 70 BMPTFSI 71 and EMIMEtSO 4 . 72 Fig.…”
Section: Bulk Defectsmentioning
confidence: 99%
“…ILs were the most common additives utilized for defect passivation in the past year due to their simultaneous interaction with both positively and negatively charged defects by counter ions, as well as good conductivity and solubility. These ionic liquids are composed of N-heterocyclic-type cations containing imidazolium, 31,65–68 pyridinium, 69 pyrrolidinium 70 and piperidinium groups, 71 and various types of anions, as seen in Fig. 8.…”
Section: Defect Passivationmentioning
confidence: 99%
“…The new third-generation solar cells, such as perovskite solar cells (PSCs), dye-sensitized solar cells, and quantum dot solar cells, have received increasing interests recently as a result of the facile fabrication process, low-cost raw material, and superior theoretical PCEs. In particular, PSCs with lead (Pb)-based halide perovskites as light absorbers exhibit several unique and excellent optical/electronic properties, including adjustable band gaps, high optical absorption coefficients, high mobility, and long diffusion length of charge carriers, leading to a rapid boosting rate of PCEs of PSCs from 3.8 to 25.7% in the last 14 years. Therefore, the newly developed PSCs are considered as the most potential replacements to traditional silicon-based solar cells for large-scale and sustainable photovoltaic power generation. , Although the PCEs of Pb-based PSCs have reached 25.7% recently, the large-scale applications of Pb-based organic–inorganic hybrid PSCs still face many crucial challenges. First, the band gaps of Pb-based organic–inorganic perovskites currently used in high-performance PSCs are generally 1.5–1.6 eV, which are much larger than the theoretical optimal band gap of 1.3–1.4 eV for solar cells calculated according to the Shockley–Queisser (S–Q) theory . Second, the toxicity of Pb is extremely harmful to the environment and humans. To overcome these problems, numerous researchers are trying to develop new Pb-free or Pb-less halide perovskites using non-toxic metals, including tin (Sn), bismuth (Bi), and germanium (Ge), to achieve sustainable and clean perovskite photovoltaics. Among various alternatives to Pb 2+ cations, Sn 2+ cations have similar electronic structures to Pb 2+ and comparable ion radii (the ionic radii of Sn 2+ and Pb 2+ are 110 and 119 pm, respectively). Therefore, partial or complete replacement of Pb 2+ in perovskites by Sn 2+ will not lead to significant lattice distortions in the perovskite structure . In addition, the band gaps of Pb–Sn perovskites can be easily adjusted between 1.17 and 1.55 eV by tailoring the Sn/Pb ratios, thereby extending the sunlight absorption range of Pb–Sn perovskites to the near-infrared region .…”
Section: Introductionmentioning
confidence: 99%